2017
DOI: 10.1016/j.gie.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety during sedation by anesthesia professionals during routine upper endoscopy and colonoscopy: an analysis of 1.38 million procedures

Abstract: Within the confines of the SAE definitions used, use of anesthesia professionals does not appear to bring a safety benefit to patients receiving colonoscopy and is associated with an increased SAE risk for ASA I, II, and III patients undergoing EGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
3
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 21 publications
(28 reference statements)
2
61
3
12
Order By: Relevance
“…However, the use of anesthesia service does not guarantee a safety benefit to patients. In fact, the overall risk of complications after colonoscopy is higher when patients receive anesthesia services related to those who receive non‐anesthesia sedation . In a prospective cohort study, Wernli et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of anesthesia service does not guarantee a safety benefit to patients. In fact, the overall risk of complications after colonoscopy is higher when patients receive anesthesia services related to those who receive non‐anesthesia sedation . In a prospective cohort study, Wernli et al .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the overall risk of complications after colonoscopy is higher when patients receive anesthesia services related to those who receive non-anesthesia sedation. [23][24][25] In a prospective cohort study, Wernli et al found that the use of anesthesia service was associated with a 13% increase in the risk of any complication within 30 days after colonoscopy (95% confidence interval [CI], 1.12-1.14) and was associated specifically with an increased risk of perforation (odds ratio [OR], 1.07; 95% CI, 1.00-1.15), hemorrhage (OR, 1.28; 95% CI, 1.27-1.30), abdominal pain (OR, 1.07; 95% CI, 1.05-1.08), complications secondary to anesthesia (OR, 1.15; 95% CI, 1.05-1.28), and stroke (OR, 1.04; 95% CI, 1.00-1.08). 24 Additionally, the use of anesthesia service was found to be associated with a higher risk of serious adverse events for American Society of Anesthesiology I, II, and III subjects undergoing EGD than those who received endoscopist-directed sedation.…”
Section: Sequence For Bidirectional Endoscopymentioning
confidence: 99%
“…The sedation procedure for SLE is summarized in the Supplementary Data S4. Any SLE‐associated adverse events (AEs) were evaluated (Supplementary Data S5) . During the SLE immediate endoscopic therapy was performed to control bleeding when AVB occurred.…”
Section: Methodsmentioning
confidence: 99%
“…González-Huix (18) The crucial fact underlying this reflection by González-Huix (18), ill-informed in our view, is that Vargo (17) compared morbidity in mainly mild-moderate endoscopist-led sedation versus anesthesiologist-administered deep sedation with propofol and general anesthesia. Both unfortunately and inconceivably, González-Huix made the serious statistical error of granting validity to a comparison between sharply different, hence incomparable cohorts in terms of variables.…”
Section: Sedation-related Morbidity and Mortality In Endoscopic Procementioning
confidence: 99%
“…The technique's safety when administered by non-anesthesiologists has traditionally raised controversy, usually disguised as scientificism when the real issue is mainly financial in nature, often covered up by dubious debates on the financial sustainability of the health system (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%